CONTESTING THE AUTHENTICITY OF THE HADITH SANAD: An Analysis of Leone Caetani’s Thought - Muhammad, Muhammad (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2020)
Abstract: One of the most heated debate on the Prophet Traditions criticism is the issue of concerning the chain of transmitter or what is popularly known as sanad which consequently determine the validity of a hadith of the Prophet Muhammad. Even Muslim scholars consider sanad to be part of the religion of Islam. In contrast to this stand, Leone Caetani, one of the Italian orientalists who is famous for his historical works on Islam, tried to blatantly criticize the chain of transmitters of the hadith as well as review them in an approach and method he himself promoted. This paper attempts to explore L. Caetani’s thoughts about the chain of transmitter of the Prophetic Traditions by applying literature study and descriptive-analytic methods. The result of this research is that L. Caetani assumes that sanad is not an integral part of the teaching of Islam but Muslim scholars but rather an adoption from the Arab tradition. In addition, it also implies that the existence of sanad is only the image of the name of the Prophet Muhammad and his narrators, and the narrators of hadith are people who cannot be followed and do a lot of practice of falsification in his narrations.Keywords: Leone Caetani, orientalis, sanad, hadis